Social networking sites in cyberspace community in Malaysia / Abdul Rauf Ridzuan…[et.al] - Ridzuan, Abdul Rauf; Abu Bakar, Aziyah; Abu Bakar, Hilmi; Ismail, Shafinar; Ridzuan, Abdul Rahim (Faculty of Communication & Media Studies, 2019)
This study is done in order to find the level of social networking sites among multiethnic users in Malaysia. Social networking sites are chosen as they bring many benefits to the users. This study used social capital theory as foundations theories for model development. The minimum sample size was determined through G⃰Power analysis. The study involved 482 respondents, selected through a cluster sampling technique involving three main ethnics in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables were measured through scales previously used by other researchers. SPSSS ver. 20 software was used in the analysis. Results of the SPSS indicated that the level of SNS, three out of four factors namely quality, intimacy, and interaction in SNS show very high level.